2021
DOI: 10.1088/1755-1315/712/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

The trend of hemoglobin levels in nasopharyngeal cancer patients treated with chemotherapy in low human development index region in Indonesia

Abstract: Nasopharyngeal cancer (NPC) is a malignant tumor in the epithelial cell of the nasopharynx. Globally, the incidence was around 80,000 new cases annually or it composed 0.7% of cancer cases in the world. In locally advanced cases, chemotherapy and radiotherapy is a treatment of choice for this cancer. Chemotherapy could be given before the radiotherapy, or simultaneous, or after the radiotherapy. Chemotherapy can affect the hemoglobin levels by inducing a suppressive effect on bone marrow and a toxic effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Kadriyan et al found that 82.5% NPC patient had anemia, most of them were mild 57.5% [17]. In the study of haemogblobin levels among NPC patients who undergoing chemotherapy, found that Hb levels decreased significantly after six courses chemotherapy [22].…”
Section: Discussionmentioning
confidence: 98%
“…Kadriyan et al found that 82.5% NPC patient had anemia, most of them were mild 57.5% [17]. In the study of haemogblobin levels among NPC patients who undergoing chemotherapy, found that Hb levels decreased significantly after six courses chemotherapy [22].…”
Section: Discussionmentioning
confidence: 98%